Peran Filsafat Pendidikan dalam Membentuk Kurikulum Merdeka Belajar dalam Pengembangan Teori dan Praktik Pendidikan di Indonesia - Chandra Gumilar; Ahmad Thoriq; Muhammad Mardiyansah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to discuss the role of educational philosophy in the development of educational theory and practice in Indonesia. Education is an essential component of human life. Education is critical in shaping human character and traits. The author employs qualitative research techniques. The author employs a literature review as a research method, while perusing and observing multiple written sources of information associated to the topic of educational philosophy's role in the formation of the Independent Learning Curriculum in the development of educational theory and practice in Indonesia. According to the research findings, the Independent Learning Curriculum is a curriculum designed by the Ministry of Education, Culture, Research, and Technology to give educational institutions flexibility in establishing a curriculum based on their unique requirements and features. The autonomous Learning Curriculum embodies the ethos of autonomous learning, specifically the spirit of student-centered learning. This paper concludes that theme learning is one of the learning approaches used in the Merdeka Belajar curriculum. This is consistent with the progressive educational concept, which holds that education must be focused on students' needs and interests.